Numerical modeling of the prestressing losses in prestressed concrete beams by modal analysis method - Djeffal, Hamza; Amrane, Mohamed-Nadir (Journal of Applied Engineering Science & Technology, 2018)
In this paper, a numerical modal analysis method is carried out to investigate the effect of cable strain loss on the natural frequencies in prestressed concrete beams. A simply supported concrete beam is modeled using the commercial finite element code ABAQUS. The beam is composed of concrete and prestressing strands. Firstly, a general geometrically nonlinear static analysis is carried out on the beam in order to obtain the camber deflection under different prestressing magnitudes. The obtained equilibrium configuration is then used to perform a linear and nonlinear modal analysis. Thereby, a three dimensional finite element C3D8 is used for the concrete in combination with a damaged plasticity model (CDP) are considered. Whereas, the prestressing strands are modeled with an embedded T2D2 truss element. The obtained results show a good agreement with previous numerical and experimental works in literature. Furthermore, the study showed that the safety of prestressed beams depend mainly on the level of prestressing load.